Self Control Pada Remaja Gamers Game Online Di Kecamatan Medan Marelan - Fachriza, Abdi; Alfita, Laili (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to describe self-control among adolescent online game gamers in Medan Marelan District. This study uses a quantitative descriptive research method. The subjects of this study were adolescent online game gamers in Medan Marelan District. The number of samples was 45 people. The data collection technique used the Incidental technique. The data collection technique employed a Likert scale model, incorporating a self-control scale. Data analysis used descriptive Frequency. The results of the data analysis showed a high level of self-control, namely 62% of respondents, 38% were in the medium category, and none were classified as low. The empirical mean value of self-control was 70.91, higher than the hypothetical mean of 58, with a standard deviation of 12, which indicates that, in general, adolescents have good self-control abilities in dealing with the urge to play games. In addition, the reliability of the self-control scale shows an Alpha coefficient value of 0.857, which means it has high internal consistency. The results of the analysis show that even though teenagers actively play online games, the majority of them are still able to control themselves well, both in terms of behavior, cognition, and decision-making.